Is computer field mature enough to be used as a tool in psychology? - Hosomi, Daniel Y.; Mota, Larissa B.; Wechsler, Solange M.; Azevedo, Helio (Anais do Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software (WASHES); 2023: Anais do VIII Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software, 2023)
The last two decades have shown an increasing number of studies involving “virtual psychotherapists” and robot caregivers of humans with cognitive, social, behavioral deficits or some other type of disorder. A characteristic of these studies is the need to combine actors of the computer, psychology and psychiatry areas. To establish the needs and contributions of these actors we conducted searches in two different databases: PsycoInfo of the American Psychological Association (APA) and Web of Science of the Clarivate Analytics. If, on the one hand, this analysis reveals the fundamental contribution of psychology in the development of applications to meet the demand for virtual agents and social robots, on the other hand, the analysis also identified the contributions and factors that still need to be addressed to enable the widespread use of these agents as a support tool in psychology and psychiatry clinics.